Understanding interactions between Automated Road Transport Systems and other road users: A video analysis. (October 2019) - Madigan, Ruth; Nordhoff, Sina; Fox, Charles; Ezzati Amini, Roja; Louw, Tyron; Wilbrink, Marc; Schieben, Anna; Merat, Natasha
Highlights: Video analysis of interactions between automated vehicles (AVs) and other road users. Investigation of the effects of road infrastructure and road user characteristics. Road infrastructure had a major impact on road users' trajectory decisions while approaching an AV. Demographic differences in interaction patterns observed. Implications for designers and developers of automated transport systems are discussed. Abstract: If automated vehicles (AVs) are to move efficiently through the traffic environment, there is a need for them to interact and communicate with other road users in a comprehensible and predictable manner. For this reason, an understanding of the interaction requirements of other road users is needed. The current study investigated these requirements through an analysis of 22 h of video footage of the CityMobil2 AV demonstrations in La Rochelle (France) and Trikala (Greece). Manual and automated video-analysis techniques were used to identify typical interaction patterns between AVs and other road users. Results indicate that road infrastructure and road user factors had a major impact on the type of interactions that arose between AVs and other road users. Road infrastructure features such as road width, and the presence or absence of zebra crossings had an impact on road users' trajectory decisions while approaching an AV. Where possible, pedestrians and cyclists appeared to leave as much space as possible between their trajectories and that of the AV. However, in situations where the infrastructure did not allow for the separation of traffic, risky behaviours were more likely to emerge, with cyclists, in particular, travelling closely alongside the AVs on narrow parts of the road, rather than waiting for the AV to pass. In addition, the types of interaction varied considerably across socio-demographic groups, with females and older users more likely to show cautionary behaviour around the AVs than males, or younger road users. Overall, the results highlight the importance of implementing the correct infrastructure to support the safe introduction of AVs, while also ensuring that the behaviour of the AV matches other road users' expectations as closely as possible in order to avoid traffic conflicts.